2009
DOI: 10.3109/17549500903312107
|View full text |Cite
|
Sign up to set email alerts
|

“It's not everyday that parents get a chance to talk like this”: Exploring parents' perceptions and expectations of speech-language pathology services for children with intellectual disability

Abstract: Tailoring the delivery of disability services to the preferences and requirements of service users allows for more effective partnerships. The aim of this research was to explore parents' perceptions and the expectations of their child's speech-language pathology (SLP) within an intellectual disability service. Parents of school-aged children with intellectual disability who received a SLP service in Ireland participated in the research: 17 parents participated in focus groups and 103 parents answered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Although there are well-established differences between LI and ASD as diagnostic categories, there is also increasing recognition of the overlap in the characteristics of children with LI and those with ASD (Bishop 2010, Ellis Weismer 2013. Previous studies have typically examined the perspectives either of parents of children with LI or of parents of children with ASD (Auert et al 2012, Brookman-Frazee et al 2012, Carroll 2010, Dillon and Underwood 2012. The present study, by contrast, was designed to compare the perspectives of parents of children with either LI or ASD who were placed in comparable types of mainstream educational provision.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are well-established differences between LI and ASD as diagnostic categories, there is also increasing recognition of the overlap in the characteristics of children with LI and those with ASD (Bishop 2010, Ellis Weismer 2013. Previous studies have typically examined the perspectives either of parents of children with LI or of parents of children with ASD (Auert et al 2012, Brookman-Frazee et al 2012, Carroll 2010, Dillon and Underwood 2012. The present study, by contrast, was designed to compare the perspectives of parents of children with either LI or ASD who were placed in comparable types of mainstream educational provision.…”
Section: The Studymentioning
confidence: 99%
“…, Brookman‐Frazee et al . , Carroll , Dillon and Underwood ). The present study, by contrast, was designed to compare the perspectives of parents of children with either LI or ASD who were placed in comparable types of mainstream educational provision.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ‘there has been a long history in speech and language therapy of working collaboratively with parents’ (Bowen and Cupples : 246) and it is widely accepted to be best‐practice and an integral component of speech–language therapy services (Crais et al . , Carroll ). Research indicates that parental involvement is effective in intervention for other types of early communication disorders, such as language delay and stuttering (e.g., Girolametto , Onslow et al .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, parents could be included to supplement the intervention delivered by SLTs to ensure the provision of intervention at an optimum evidence-based intensity (Lawler et al 2013, Joffe andPring 2008). Indeed, 'there has been a long history in speech and language therapy of working collaboratively with parents' (Bowen and Cupples 2004: 246) and it is widely accepted to be best-practice and an integral component of speech-language therapy services (Crais et al 2006, Carroll 2010. Research indicates that parental involvement is effective in intervention for other types of early communication disorders, such as language delay and stuttering (e.g., Girolametto 1988, Onslow et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…41,45 It has been suggested that parents may vary in their willingness and/or capacity to assume the role of 'co-therapist'. [48][49][50][51] Notions of feeling overburdened by the requirements of a therapy regime, and a lack of ongoing training and support, have also been reported. 52 In terms of work within the existing NIHR portfolio, a study 47 funded as part of the Research for Patient Benefit programme has been recently published, which evaluated a training intervention for parents and school staff on postural management.…”
Section: Study Limitationsmentioning
confidence: 99%